Truths and myths concerning affinity between asphalt and aggregate tested in accordance with PN-EN 12697-11 - Zięba, Monika; Witczak, Sebastian (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Very important element, which shall be taken into account while designing asphalt mixes, is the physicochemical affinity of asphalt binder to aggregate. There are many test methods for its determination, but the results can be totally different. During the two years research program, there were determined the influence of different factors on the test results, and the possibility of fulfilling the requirements given in different countries.